Electronic form of citizens' appeal as an indicator of digital transformation of public administration - Ківалов, Сергій Васильович; Ківалов, С. В.; Кивалов, Сергей Васильевич; Kivalov, Serhii V. (Mykolas Romeris University, 2020)
In Ukraine, the appeal of citizens to the subjects of office is an indicator of the democratization of the entire system of public administration, its openness, effectiveness, and efficiency. The official data on the number of appeals filed with the Cabinet of Ministers of Ukraine from 2017 to 2019 was analyzed, using correlation analysis, Pearson’s chi-squared criterion, and theoretical and empirical distribution method. It was established that the prevailing form of citizens’ appeal to the Cabinet of Ministers of Ukraine in 2019 was the electronic form. The amount of using the electronic form has changed significantly from 2017 to 2019: the value of the Pearson’s Chi-squared criterion is 332.622, p <0.001. Moreover, it was determined that the value of the opportunity to focus on the application itself, and not on the accompanying formal application procedures, is the only significant harbinger of the thesis that using electronic forms makes the participation of citizens in public administration better. As a result of the study, it is proved that in Ukraine the distribution of the values of citizens’ appeals to the Cabinet of Ministers of Ukraine is different depending on the sphere of public relations; citizens’ appeals to the Cabinet of Ministers of Ukraine mostly concern the sphere of social protection: the value of Pearson’s Chi-squared in 2019 is 27.203, p <0.01; in 2018 – 29.855, p <0.01; in 2017 – 28.65, p <0.01. Besides, it was determined that the changes in the distribution of appeals to the Cabinet of Ministers of Ukraine for 2017-2019 depending on the sphere of public relations were not identified.

В Україні звернення громадян до суб’єктів управління є показником демократизації всієї системи державного управління, її відкритості, дієвості та ефективності. Проаналізовано офіційні дані щодо кількості звернень, поданих до Кабінету Міністрів України з 2017 по 2019 роки, за допомогою кореляційного аналізу, критерію хі-квадрат Пірсона та теоретичного та емпіричного методу розподілу. Встановлено, що переважаючою формою звернення громадян до Кабінету Міністрів України у 2019 році була електронна форма. Обсяг використання електронної форми істотно змінився з 2017 по 2019 рік: значення критерію узгодженості Пірсона (критерію хі-квадрат Пірсона) становить 332,622, p <0,001. Більше того, було визначено, що цінність можливості зосередитися на самому зверненні, а не на супутніх формальних процедурах подачі заявки, є єдиним суттєвим передвісником тези про те, що використання електронних форм покращує участь громадян у державному управлінні. У результаті дослідження доведено, що в Україні розподіл значень звернень громадян до Кабінету Міністрів України різний залежно від сфери суспільних відносин; звернення громадян до Кабінету Міністрів України переважно стосуються сфери соціального захисту: значення хі-квадрата Пірсона у 2019 році становить 27,203, p <0,01; у 2018 р. – 29,855, р <0,01; у 2017 р. – 28,65, р <0,01. Крім того, зазначено, що не визначено зміни у розподілі звернень до Кабінету Міністрів України на 2017-2019 роки залежно від сфери суспільних відносин.
Kivalov S. Electronic form of citizens' appeal as an indicator of digital transformation of public administration / S. Kivalov // Public Policy and Administration. - Mykolas Romeris University, 2020. - Vol. 19. - Issue 4. - P. 52-63.
Keywords: democratization; legal system; the Pearson’s Chi-squared criterion; E-government concept; демократизація; правова система; критерій узгодженості Пірсона; концепція електронного уряду; Research Subject Categories::LAW/JURISPRUDENCE